A novel approach: Supercritical carbon dioxide + ethanol extraction to improve techno‐functionalities of pea protein isolate. Issue 1 (20th October 2021) - Vatansever, Serap; Ohm, Jae‐Bom; Simsek, Senay; Hall, Clifford
Abstract: Background and objectives: Dry peas ( Pisum sativum L.) are an excellent source of functional proteins. Supercritical carbon dioxide +ethanol (SC‐CO2 +EtOH) extraction was reported as a successful deflavoring approach to improve sensory attributes of pea flour. However, the effects of this extraction system on nutrient, structural, thermal, and functional characteristics of pea protein isolate (PPI) extracted from deflavored whole pea flour (DWPF) were not examined; thus, the focus of this study was to evaluate these characteristics. Findings: Deflavored PPI (DPPI) obtained from SC‐CO2 +EtOH extraction had significantly ( p < .05) higher moisture, total starch, and protein contents than nonextracted PPI (NPPI). Fourier transform infrared (FTIR) wavelengths associated with lipids were more intense in NPPI compared with DPPI. Significant higher denaturation temperature, protein solubility, emulsion, and foaming properties of DPPI were obtained. Structural changes in DPPI were recorded based on FTIR spectra, X‐ray diffraction pattern, and scanning electron microscopy. Conclusion: SC‐CO2 +EtOH extraction as a green technology significantly impacted the proximate composition, structural, thermal, and functional characteristic of PPI. Significance and novelty: Effects of SC‐CO2 +EtOH extraction on pea protein characteristics have not reported in the literature. The results are crucial for adoption of this technology for physical modification of plant proteins.